Pechini derived multifunctional MgO based chromate nanocomposites for superior brilliant green dye adsorption - Maram T. Basha; Mortaga M. Abou-Krisha; Fawaz A. Saad; Reem K. Shah; Ehab A. Abdelrahman (Scientific Reports)
Abstract The environmental threat posed by brilliant green dye necessitates the development of advanced materials with superior adsorption efficiency and structural tunability. In this study, two novel multifunctional nanocomposites, MgO/CaCrO4/CaCO3/CaO/C (MC600) and MgO/Ca5(CrO4)3O0.5/C (MC800), were successfully fabricated using a tailored Pechini sol–gel method. This work introduces a temperature-controlled phase-engineering approach that induces distinct structural evolution, from multiphase composites at 600 °C to highly crystalline, thermodynamically stable phases at 800 °C. The average crystallite sizes, estimated from X-ray diffraction (XRD) patterns, were found to be 60.68 nm for MC600 and 65.88 nm for MC800. Field emission scanning electron microscope (FE-SEM) showed that MC600 had agglomerated particles with rough textures, whereas MC800 displayed more defined spherical particles with improved homogeneity. The results were consistent with those obtained from high-resolution transmission electron microscope (HR-TEM) imaging, showing irregular, highly agglomerated shapes in MC600 and well-defined, mostly spherical to quasi-hexagonal particles in MC800, reflecting enhanced crystallinity and reduced aggregation. Adsorption studies demonstrated excellent performance in brilliant green removal, with maximum capacities of 246.91 mg/g for MC600 and 229.89 mg/g for MC800, outperforming some conventional adsorbents. The adsorption mechanism was spontaneous, physical, and exothermic, following the Langmuir-based adsorption model and first-order kinetic model kinetics. Moreover, the MC600 nanocomposite exhibited good reusability, maintaining over 85% removal efficiency after five consecutive adsorption–desorption cycles.